An efficient beamforming design for multipair full-duplex relaying systems - Hyeon Min Kim; Van-Dinh Nguyen; Oh-Soon Shin (ICT Express, 2017)
We consider a decode-and-forward full-duplex relaying system for multiple pairs of users. Our objective is to maximize the minimum achievable rate for all user pairs under the transmit power constraints. We propose an iterative algorithm to solve the nonconvex max–min problem. In particular, the original problem is converted into successive convex programs by using an inner approximation method such that each iteration involves only a simple convex quadratic program. We show that the proposed algorithm improves achievement of the objective iteratively while guaranteeing convergence. Simulation results demonstrate that the proposed algorithm provides higher rates than both half-duplex and full-duplex relaying based on zero-forcing do.